2018
DOI: 10.5466/ijoms.16.31
|View full text |Cite
|
Sign up to set email alerts
|

<b>Caspase-mediated Apoptosis by Compressive Force Induces RANKL in Cementoblasts </b>

Abstract: Orthodontic root resorption (ORR) is one of the serious adverse events related to orthodontic treatment. Caspases are important effector molecules that mediate the process of apoptosis. However, the relationship between the mechanism underlying ORR and apoptosis in the cementum has not been clarified. In this study, human cementoblast-like cells (HCEMs) were cultured and subjected to pressure conditions assumed during orthodontic tooth movement in vitro. We then examined the effect of compressive force on casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These findings are consistent with previous in vivo and in vitro studies, which have demonstrated that osteocyte apoptosis occurs under the orthodontic compressive force (Hoshi et al, 2014; Sakai et al, 2009). Moreover, compression can trigger apoptosis in other periodontal tissue cells like cementoblasts, osteoblasts and periodontal ligament cells (PDLCs) (Funakoshi et al, 2013; Goga et al, 2006; Yamaguchi et al, 2018). Intriguingly, the minimum force that caused osteocyte apoptosis (0.125 kPa, equivalent to 1.275 g/cm 2 ) is relatively close to that of cementoblasts (2.0 g/cm 2 ) and PDLCs (1.0 g/cm 2 ), but much higher than that of osteoblasts (2.04 × 10 −4 N/cm 2 , nearly 0.01 g/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous in vivo and in vitro studies, which have demonstrated that osteocyte apoptosis occurs under the orthodontic compressive force (Hoshi et al, 2014; Sakai et al, 2009). Moreover, compression can trigger apoptosis in other periodontal tissue cells like cementoblasts, osteoblasts and periodontal ligament cells (PDLCs) (Funakoshi et al, 2013; Goga et al, 2006; Yamaguchi et al, 2018). Intriguingly, the minimum force that caused osteocyte apoptosis (0.125 kPa, equivalent to 1.275 g/cm 2 ) is relatively close to that of cementoblasts (2.0 g/cm 2 ) and PDLCs (1.0 g/cm 2 ), but much higher than that of osteoblasts (2.04 × 10 −4 N/cm 2 , nearly 0.01 g/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐physiological mechanical stimuli are known to promote apoptosis through the mitochondrial‐ or death‐receptor‐mediated signaling pathways in several periodontal cells (Funakoshi et al, 2013; Song et al, 2016; Yamaguchi et al, 2018). However, there have been few mechanistic studies on compressive force‐induced osteocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 For instance, a human immortalized cementoblast cell line and PDL cells significantly express RANKL under stress; [10][11][12][13][14] Orthodontic tooth movement (OTM) activates cementoblasts to induce RANKL expression. 15,16 Thus, considering the similarities between osteoclastogenesis and odontoclastogenesis, 17 osteoporosis drugs (e.g., bisphosphate, which causes direct cell death, and denosumab, an anti-RANKL antibody that prevents osteoclast formation) have been exclusively investigated to treat root resorption. 18,19 However, thus far, these drugs have not yet reached clinical application.…”
Section: Introductionmentioning
confidence: 99%